2020
DOI: 10.1038/s41598-020-68221-w
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic fabrication of microcarriers with sequential delivery of VEGF and BMP-2 for bone regeneration

Abstract: Wound instability and poor functional vascularization in bone tissue engineering lead to lack of tissue integration and ultimate failure of engineered grafts. In order to harness the regenerative potential of growth factors and stimulate bone healing, present study aims to design multifunctional cell therapy microcarriers with the capability of sequential delivery of essential growth factors, bone morphogenetic protein 2 (BMP-2) and vascular endothelial growth factor (VEGF). An on-chip double emulsion method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 92 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Microfluidics has offered an effective alternative to traditional methods to fabricate polymeric microparticles. Nowadays, microfluidics is an effective tool to generate microparticles with high monodispersity, precisely tunable structures, and excellent encapsulation efficiency ( Damiati et al, 2018 ; Dashtimoghadam et al, 2020 ). Microfluidic chips are either lab-made or commercial products made of glass, polymers, or polydimethylsiloxane (PDMS), and consist of rectangular microchannels in different dimensions that are constructed by lithography ( Damiati et al, 2018 ; Dewandre et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics has offered an effective alternative to traditional methods to fabricate polymeric microparticles. Nowadays, microfluidics is an effective tool to generate microparticles with high monodispersity, precisely tunable structures, and excellent encapsulation efficiency ( Damiati et al, 2018 ; Dashtimoghadam et al, 2020 ). Microfluidic chips are either lab-made or commercial products made of glass, polymers, or polydimethylsiloxane (PDMS), and consist of rectangular microchannels in different dimensions that are constructed by lithography ( Damiati et al, 2018 ; Dewandre et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that angiogenesis is a critical process in tissue repair and regeneration. Dashtimoghadam et al demonstrated that multifunctional cell therapy microcarriers containing mesenchymal stem cells (MSCs), endothelial cells, and vascular endothelial growth factor (VEGF) enhance the regeneration of bone tissue in vivo [43]. New blood vessel formation is a prominent process during tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that bone regeneration can be significantly improved by the combined BMP-2 and VEGF growth factors. Dashtimoghadam et al (2020) demonstrated conjugation of BMP-2 growth factor onto monodisperse polymeric microcarriers encapsulating VEGF growth factor, which displayed an additive effect on bone regeneration. Moreover, in the study of Godoy-Gallardo et al (2020) , BMP-2 was bound onto the inner polydopamine layer, whereas VEGF was immobilized onto the outer one, and the two growth factors played a synergistic effect on bone regeneration.…”
Section: Discussionmentioning
confidence: 99%